Effect of exercise training on amyloid-like protein aggregates among patients with heart failure. (11th May 2021) - Gouveia, M; Schmidt, C; Teixeira, M; Magalhaes, S; Nunes, A; Lopes, M; Vitorino, R; Ferreira, R; Santos, M; Vieira, S; Ribeiro, F
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): MG and CS were supported by a PhD FCT grant (SFRH/BD/128893/2017) and by an individual grant from CAPES [BEX 0554/14-6], respectively. This work was financially supported by the project POCI-01-0145-FEDER-030011, funded by FEDER, through COMPETE2020-POCI, and by national funds, through FCT/MCTES (PTDC/MEC-CAR/30011/2017). iBiMED is a research unit supported by the Portuguese Foundation for Science and Technology (REF: UID/BIM/04501/2020) and FEDER/Compete2020 funds). Introduction: Amyloid-like protein aggregates play a decisive role in the pathology of heart failure. Alterations in protein homeostasis, in particular, the clearance of toxic amyloid-like aggregates are emerging therapeutic targets in cardiovascular medicine. The clinical benefits of cardiac rehabilitation and exercise training are widely accepted in heart failure; however, little is known about the potential benefit of exercise training in amyloid-like protein aggregates. Purpose: To assess the effects of a moderate-intensity exercise training program on amyloid-like protein aggregates levels among patients with heart failure with reduced ejection fraction. Methods: Eighteen subjects participated in the study; eight patients (age: 66.6 ± 5.9 years; FEVE: 38.4 ± 8.9%) with heart failure with reduced ejection fraction participated in a 3-month exercise training program (2 x 60 min sessions per week of moderate-intensity aerobic and resistance exercise). Ten healthy subjects (age: 68. 4 ± 3.1 years) were recruited to an age-matched reference group.  Amyloid-like protein aggregates were assessed before and after 3 months of exercise training. Clinical data, medication, anthropometrics, and cardiorespiratory fitness were also assessed. Thioflavin T (ThT) dye fluorescence was used to quantify the plasma levels of amyloid-like aggregates and the Fourier transform infrared spectroscopy (FTIR) was applied to evaluate the conformation of cross-β-sheet structures characteristic of amyloid protein aggregates. Results: Exercise program improved cardiorespiratory fitness by 14.0 ± 17.1% (17.4 ± 3.2 to 19.7 ± 2.9 ml/kg/min) and reduced NT-proBNP levels by 16.5% (34.2) (median concentration of 632 pg/mL (720.8) to 517.5 pg/mL (707.0)) in the heart failure patients. A slight decrease of amyloid-like aggregates levels was observed in post-exercise training samples (a reduction of 3.1%); interestingly, after the exercise training program, the heart failure patients showed levels of amyloid-like aggregates similar to the reference group (1132.0 ± 114.2 vs. 1094.8 ± 132.9 a.u.). Additionally, the PLS-R multivariate analysis of the amide I region of the FTIR spectra revealed enrichment of antiparallel β-sheets (1693 cm-1) assigned to amyloid-like oligomers in the samples of heart failure patients before, but not after, the exercise program. Of note, oligomeric species, as intermediates of amyloid assembly, can contribute to the increase of amyloid burden, but also, some have been reported to be highly reactive and toxic to cells, being key elements of amyloid pathogenesis. Conclusions:  Our preliminary results indicate that 3 months of exercise training may have significant effects on amyloid-like oligomers, and start hindering the formation of the larger ThT-positive aggregates among patients with heart failure.